Do Lecture Pace and PowerPoint Detail Affect Students' Comprehension of and Memory for a PowerPoint-Assisted Lecture? - Xiong, Amy K.; Koktavy, Nicole D.; Maule, Carson A.; Steffes, Amy E.; Chase, Johnathan C.; Halberg, Ian A.; Zellhoefer, Ashley S. (My University, 2009)
Research on the effectiveness of PowerPoint as an aid to leacture presentations is rarely guided by cognitive theory. However, Mayer's cognitive theory of multimedia learning is well-suited to guide the design of PowerPoint presentations and generating predictions about the effects of those presentatins on learners. This experiment tested the effects of either a fast or slow lecture accompanied by either a detailed or outlined PowerPoint display of the information.
Color poster with text and graph describing research conducted by Nicole D. Koktavy et al., advised by Kathryn L. Hamilton and Allen H. Keniston.
Keywords: Teaching--Audio-visual aids; Media programs (Education)--Evaluation; Posters; Audio-visual education--Evaluation; Learning, Psychology of; Computer-assisted instruction--Evaluation; Microsoft PowerPoint (Computer file)--Educational aspects; Learning--Audio-visual aids